2012
DOI: 10.2340/00015555-1233
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Methotrexate in Psoriasis

Abstract: Methotrexate (MTX) is the most commonly used systemic therapy for psoriasis. The drug is a folie acid antagonist and the main effect on psoriasis is thought to be inhibition of lymphatic cell proliferation (1). Due to its anti-inflammatory effect, MTX may also have a protective effect against cardiovascular disease (2,3). MTX is generally well tolerated, but common, minor adverse reactions are nausea, loss of appetite, and fatigue. Major toxicities include myelosuppression, hepatotoxicity, and pulmonary flbros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
8
0
4
Order By: Relevance
“…2 In our study, the vast majority of patients received folic acid. The study by Due et al, 14 also reported side-effects as the main reason for MTX discontinuation. In their study, only 60Á3% of the patients received folic acid supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…2 In our study, the vast majority of patients received folic acid. The study by Due et al, 14 also reported side-effects as the main reason for MTX discontinuation. In their study, only 60Á3% of the patients received folic acid supplementation.…”
Section: Discussionmentioning
confidence: 95%
“…According to a EUROPSO membership survey, high satisfaction was documented more frequently for methotrexate (30%) than for cyclosporine (28%) and fumaric acid (26%) (15). Methotrexate may have PASI 75 response rates of up to 60% (5), but bears a significant risk of adverse events which are the most common reason for treatment discontinuation (36).…”
Section: Discussionmentioning
confidence: 98%
“…Long‐term use of biologics is associated with a lower rate of adverse events than long‐term use of traditional systemic antipsoriatic drugs . While there have only been few studies comparing the reasons for discontinuation of different traditional therapies , reasons for terminating individual traditional agents have been examined in several publications, all of which identified adverse events as the most common cause . In our cohort, all treatment courses with CyA were stopped, most commonly due to adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, it would be highly desirable to achieve long‐term disease control by continued administration of a single systemic drug. However, discontinuation or switching of systemic medications because of primary or secondary treatment failure or adverse events is common . Treatment duration with traditional systemic agents such as CyA or MTX may also be limited by cumulative renal or hepatic toxicity .…”
Section: Introductionmentioning
confidence: 99%